2021
DOI: 10.1016/j.dcn.2021.100916
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in amygdala, hippocampus and cortisol development following early caregiving adversity

Abstract: Although decades of research have shown associations between early caregiving adversity, stress physiology and limbic brain volume (e.g., amygdala, hippocampus), the developmental trajectories of these phenotypes are not well characterized. In the current study, we used an accelerated longitudinal design to assess the development of stress physiology, amygdala, and hippocampal volume following early institutional care. Previously Institutionalized (PI; N = 93) and comparison (COMP; N = 161) youth (ages 4–20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 91 publications
1
43
0
Order By: Relevance
“…Such experiences, perhaps due to subjective perceptions and processes, would then actually be threatening in nature-the lack of a clear attachment figure would cause heightened vigilance to environmental dangers. This actually fits well with results from Tottenham's group that has found postinstitutionalized children who suffered early social neglect have alterations in the amygdala, both structurally and functionally (e.g., Cohen et al, 2013;VanTieghem et al, 2021) and more recently found amygdala volume predicted later stress hormone responses (VanTieghem et al, 2021). Of important note, we believe compelling distinctions exist in non-human animal models of stress for inescapable vs. unpredictable stressors, but believe it still too early to synthesize these ideas to the exposure vs. experience distinction in humans.…”
Section: Further Consideration Of Ela Amygdala Neurobiology and Clinical Practicesupporting
confidence: 90%
See 1 more Smart Citation
“…Such experiences, perhaps due to subjective perceptions and processes, would then actually be threatening in nature-the lack of a clear attachment figure would cause heightened vigilance to environmental dangers. This actually fits well with results from Tottenham's group that has found postinstitutionalized children who suffered early social neglect have alterations in the amygdala, both structurally and functionally (e.g., Cohen et al, 2013;VanTieghem et al, 2021) and more recently found amygdala volume predicted later stress hormone responses (VanTieghem et al, 2021). Of important note, we believe compelling distinctions exist in non-human animal models of stress for inescapable vs. unpredictable stressors, but believe it still too early to synthesize these ideas to the exposure vs. experience distinction in humans.…”
Section: Further Consideration Of Ela Amygdala Neurobiology and Clinical Practicesupporting
confidence: 90%
“…For example, recent longitudinal work (Whittle et al, 2013) suggest a slowing of growth of the amygdala after ELA. Particularly important to highlight, youth who suffered early social neglect, one form of ELA, had a reduced growth rate of the amygdala, resulting in smaller volumes by adolescence (VanTieghem et al, 2021) and it is as-yet unknown if this represents a delay or a missed critical period to learn fear and safety.…”
Section: What Is the State-of-science Of Adversity's Impact Of The Amygdala? What Might Be Causing These Inconsistencies?mentioning
confidence: 99%
“…For each scan, we calculated fear > baseline, neutral > baseline, and fear > neutral contrasts. We used native-space bilateral amygdala masks generated using Freesurfer (v6.0; Fischl, 2012) by VanTieghem et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Animal models have demonstrated that concentrations of glucocorticoid and noradrenaline receptors can be found within subnuclei (i.e., basolateral complex) and subfields (e.g., dentate gyrus) of the amygdala and hippocampus ( Johnson et al, 2005 ; McEwen et al, 1975 ), making them particularly vulnerable to stress-related alterations in their morphology and function ( Vouimba et al, 2007 ). In humans, volumetric reductions in the hippocampus and amygdala following traumatic experiences have been reported in pediatric samples from longitudinal and cross-sectional studies ( Phillips et al, 2021 ; Saxbe et al, 2018 ; VanTieghem, 2021 ; Veer et al, 2015 ; Weissman et al, 2020 ). While most studies examining morphological properties of amygdala and hippocampus following trauma have largely focused on samples at elevated risk for or with established psychopathology symptomology (e.g., Logue et al, 2018 ), only a third of individuals with histories of trauma actually develop clinical levels of psychopathology ( MacMillan et al, 2001 ).…”
Section: Introductionmentioning
confidence: 98%